1999
DOI: 10.1176/ps.50.10.1297
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Closing a State Psychiatric Hospital on the County Mental Health System and Its Clients

Abstract: The hospital closure and infusion of funds into community services produced desired growth of those services. The project reduced reliance on state psychiatric hospitalization and demonstrated that persons with serious mental illness can be effectively treated and maintained in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Apesar de as diferenças, a filosofia da reforma psiquiátri-ca tem sido fundamentada nos princípios básicos dos cuidados na comunidade: desinstitucionalização e diminuição dos leitos hospitalares, desenvolvimento de programas e serviços alternativos, integração com serviços comunitários e demais serviços de saúde e acesso à medicação 17,18 . Trabalhos realizados em vários países têm indicado que os pacientes desospitalizados podem ser mantidos na comunidade [19][20][21] , demonstrando melhora nas habilidades de vida diária e na interação social 3,[22][23][24] , no nível global de funcionamento 21,22,25 e na qualidade de vida [20][21][22][23][24][25][26][27][29][30][31]40 . Em tratamentos de base comunitária, a autonomia e o desempenho geral dos pacientes podem ser melhorados,…”
Section: A Assistência Psiquiátrica Na Atualidadeunclassified
“…Apesar de as diferenças, a filosofia da reforma psiquiátri-ca tem sido fundamentada nos princípios básicos dos cuidados na comunidade: desinstitucionalização e diminuição dos leitos hospitalares, desenvolvimento de programas e serviços alternativos, integração com serviços comunitários e demais serviços de saúde e acesso à medicação 17,18 . Trabalhos realizados em vários países têm indicado que os pacientes desospitalizados podem ser mantidos na comunidade [19][20][21] , demonstrando melhora nas habilidades de vida diária e na interação social 3,[22][23][24] , no nível global de funcionamento 21,22,25 e na qualidade de vida [20][21][22][23][24][25][26][27][29][30][31]40 . Em tratamentos de base comunitária, a autonomia e o desempenho geral dos pacientes podem ser melhorados,…”
Section: A Assistência Psiquiátrica Na Atualidadeunclassified
“…Indeed, if we look at all the other forces that have been outlined here, continued deinstitutionalisation cannot be attributed to economic considerations alone, but also to clinical, scientific, and humanistic factors which together render the trend ineluctable. Table III shows the domains of the mental health services evaluation matrix covered by four recent series of studies conducted in the UK (TAPS studies regarding the closure of two London psychiatric hospitals), the US (Central State Hospital study and studies by Kamis-Gould et al (1999) and Rothbard et al (1998) concerning the closure of the Philadelphia State Hospital), and Canada (study of the downsizing of a large psychiatric hospital in Montreal). Most of the papers stemming from the TA-PS project, especially those published in the British Journal of Psychiatry, have focussed on the patient level, on the dimensions of outcome and, to a lesser extent, process.…”
Section: Functions Of Psychiatric Hospitals and Dynamics Of Deinstitumentioning
confidence: 99%
“…Processes were documented primarily by way of detailed information on service utilisation, including hospitalisation and costs of care. (Leff et al, 1996) CSH: Central State Hospital study (McGrew, 1999) Mtl: Study of Montreal's largest psychiatric hospital (Lesage et al, 1999) PSH: Philadelphia State Hospital study (Rothbard et al, 1998 andKamis-Gould et al, 1999) Epidemiologia e Psichiatria Sociale, 9, 3, 2000 The key findings of this study involving over one thousand patients included the following: 78% of patients were discharged to supervised residential settings; less than 1% became homeless; symptoms generally changed very little; living in community-supervised residential settings allowed more autonomy; and the social networks of discharged patients grew. The overall cost for all discharged patients was slightly higher on average than if they had remained in the hospital.…”
Section: Four Recent Series Of Deinstitutionalisation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If there are sufficient community alternatives, the demand for acute care psychiatric beds should be lower. At least one study showed that the closure of a state psychiatric hospital and the subsequent reallocation of funds resulted in the growth of community services that better met the needs of the community (Kamis-Gould, Snyder, & Casey, 1999). …”
mentioning
confidence: 99%